Forecasting the relationship between stock return and financial ratio: evidence from construction companies / Fathiah Suhaini - Suhaini, Fathiah (2016)
This study aims to give the evidence of whether financial ratios are able predict the future stock return in Malaysian Stock Market. Three variables are used as a predictor of future stock return which are the Book to Market Ratio (BTM), Dividend Yield (DY) and Earning per Share (EPS). This study cover the Period of 2011 to 2015 using 30 companies in Bursa Malaysia Stock Exchange. Results from the multiple regressions analysis shows that only BTM and DY are able to predict future stock return, as EPS is insignificant. In addition, DY has superior predictive power compared to the other variables.